2013
DOI: 10.1007/s00068-013-0283-5
|View full text |Cite
|
Sign up to set email alerts
|

Indications for implant removal after fracture healing: a review of the literature

Abstract: Introduction The aim of this review was to collect and summarize published data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 68 publications
0
68
1
2
Order By: Relevance
“…Other investigations have also supported this result [5,8]. Vos et al [7] reported that implant removal is rarely indicated in asymptomatic patients because of complications such as neurovascular injury or refracture. Busam et al [1] reported that implant removal may be more difficult and may result in complications of neurovascular injury, refracture, recurrent deformity.…”
Section: To Remove the Implant Or Not?mentioning
confidence: 55%
See 2 more Smart Citations
“…Other investigations have also supported this result [5,8]. Vos et al [7] reported that implant removal is rarely indicated in asymptomatic patients because of complications such as neurovascular injury or refracture. Busam et al [1] reported that implant removal may be more difficult and may result in complications of neurovascular injury, refracture, recurrent deformity.…”
Section: To Remove the Implant Or Not?mentioning
confidence: 55%
“…In addition, due to the higher risk of complications during a second operation for implant removal (refracture/neurovascular injury/infection, etc.) [7], we do not recommend implant removal as a routine procedure after bone union unless there is significant discomfort or functional disturbance due to the implant.…”
Section: To Remove the Implant Or Not?mentioning
confidence: 95%
See 1 more Smart Citation
“…Hardware removal has been a debated topic in recent years, due to the numerous variables involved in the procedure. Vos et al 15 in a recent review concluded that the indication to remove implants after fracture healing should exist only in symptomatic patients and after a proper informed consent. In our case the evident infection and the non-union of the bone segments represented valid and unquestionable indications to operate a second time.…”
Section: Discussionmentioning
confidence: 99%
“…While some favour routine removal, others do not. 4,11,18,21 Patients' requests and symptomatic implants are typical indications for removal.…”
Section: Introductionmentioning
confidence: 99%